How to create and use rubrics for formative assessment and grading - Brookhart, Susan M., ....- (Alexandria : ASCD, 2013)
Whether you're already familiar with rubrics or not, this book is a complete resource for writing rubrics that assist with learning as well as assess it. Plus, you'll learn how to wisely select from among the many rubrics available for classroom use.
What are rubrics and why are they important? -- Common misconceptions about rubrics -- Writing or selecting effective rubrics -- General rubrics for fundamental skills -- Task-specific rubrics and scoring schemes for special purposes -- Proficiency-based rubrics for standards-based grading -- Checklists and rating scales: not rubrics, but in the family -- More examples -- Rubrics and formative assessment: sharing learning targets with students -- Rubrics and formative assessment: feedback and student self-assessment -- How to use rubrics for grading.
Includes bibliographical references and index.
Keywords: Grading and marking (Students).; Educational evaluation